Нові місцезнаходження nymphoides peltata (S.G. Gmel.) О. Kuntze (menyantheaceae) на території України - Козак, M.I. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2006)
Сообщается о пяти новых местонахождениях Nymphoides peltata в Украине. Дается характеристика его современного распространения и эколого-ценотических особенностей на территории Западной Подолии. Рассмотрены ведущие факторы антропогенного влияния и предложены мероприятия по охране сообществ вида. The article informs about five new locations of Nymphoides peltata in Ukraine. The characteristics of modern expansion and ecological cenotic peculiarities of its distribution in the territory of Western Podolia are given. The leading factors of anthropogenetic influence are considered and measures for protection of Nymphoides peltata communities are proposed.